Matched whole grain wheat and refined wheat milled products do not differ in glycemic response or gastric emptying in a randomized, crossover trial. Issue 4 (6th January 2022) - Pletsch, Elizabeth A; Hayes, Anna M R; Chegeni, Mohammad; Hamaker, Bruce R
ABSTRACT: Background: Epidemiologic and some clinical studies support the view that whole grain foods have lower glycemic response than refined grain foods. However, from the perspective of food material properties, it is not clear why whole grain cereals containing mostly insoluble and nonviscous dietary fibers (e.g., wheat) would reduce postprandial glycemia. Objectives: We hypothesized that glycemic response for whole grain wheat milled products would not differ from that of refined wheat when potentially confounding variables (wheat source, food form, particle size, viscosity) were matched. Our objective was to study the effect of whole grain wheat compared with refined wheat milled products on postprandial glycemia, gastric emptying, and subjective appetite. Methods: Using a randomized crossover design, healthy participants ( n  = 16) consumed 6 different medium-viscosity porridges made from whole grain wheat or refined wheat milled products, all from the same grain source and mill: whole wheat flour, refined wheat flour, cracked wheat, semolina, reconstituted wheat flour with fine bran, and reconstituted wheat flour with coarse bran. Postprandial glycemia, gastric emptying, and appetitive response were measured using continuous glucose monitors, the 13 C-octanoic acid (8:0) breath test, and visual analog scale (VAS) ratings. Bayes factors were implemented to draw inferences about null effects. Results: Little-to-no differences were observed in glycemic responses, with lower incremental AUC between 0 and 120 min glycemic responses only for semolina [mean difference (MD): −966 mg min/dL; 95% CI: −1775, −156 mg min/dL; P = 0.02) and cracked wheat (MD: −721 mg min/dL; 95% CI: −1426, −16 mg min/dL; P = 0.04) than for whole wheat flour porridge. Bayes factors suggested weak to strong evidence for a null effect (i.e., no effect of treatment type) in glycemic response, gastric emptying, and VAS ratings. Conclusions: Although whole grain wheat foods provide other health benefits, they did not in their natural composition confer lower postprandial glycemia or gastric emptying than their refined wheat counterparts. This trial was registered at clinicaltrials.gov as NCT03467659.